Candidate Features and Candidate Selection Patterns in Hungary, 1994–2010. Issue 1 (9th December 2017) - Papp, Zsófia
Abstract : Although 25 years have passed since the Hungarian transition of 1989–90, to date, there have been no systematic analyses of candidate characteristics and candidate selection patterns. This article asks: What candidate features do party selectorates value when deciding on candidate nominations from 1994 to 2010? I investigate the candidate selection patterns of Hungarian parties though candidates' placement on the party lists. I use an original data set containing the whole universe of candidates running in democratic elections between 1994 and 2010. I describe the Hungarian candidate scene with regard to electoral and legislative experience, age and gender of the candidates. I apply multilevel linear regressions to obtain the net effect of these characteristics on party list placements. I find first, that parties place more experienced candidates higher on the party lists. Second, selectors punish older candidates by placing them lower on party lists. Third, women also face a disadvantage in list placements: parties place men in better positions on the lists.